2019
DOI: 10.1111/nep.13247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a chronic kidney disease risk assessment service in community pharmacies

Abstract: There is significant scope for improving early detection of CKD via implementation of a community pharmacy-based CKD risk assessment service. However, a healthcare system that encourages inter-professional collaboration between community pharmacists and GPs, and provides a robust referral pathway is needed to optimise the effectiveness of this service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous studies have used point-of-care technology to evaluate CKD risk assessment in community pharmacies; however, this study was the first to evaluate the relative strength of risk factors in predicting and identifying CKD issues. 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used point-of-care technology to evaluate CKD risk assessment in community pharmacies; however, this study was the first to evaluate the relative strength of risk factors in predicting and identifying CKD issues. 21…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used point-of-care technology to evaluate CKD risk assessment in community pharmacies; however, this study was the first to evaluate the relative strength of risk factors in predicting and identifying CKD issues. 21 Moreover, 72% of patients had their medication regimen reviewed by a pharmacist. This is instrumental in helping to identify and differentially diagnose medication-related causes of CKD, in ruling out acute kidney injury requiring immediate medical attention, and identifying other drug-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Our pilot work in an Australian context involving 24 community pharmacies and 389 patients found that 52% of screened participants had moderate or high risk of developing CKD, but only 53% of them subsequently had kidney function tests via a pathology provider 29. The pilot work highlighted issues such as poor referral uptake by GPs, lack of service remuneration and absence of objective measurements for kidney function 29 30.…”
Section: Introductionmentioning
confidence: 94%
“…The use of POCT by pharmacists has been previously evaluated and demonstrated in diabetes and in patients taking warfarin 23–25. Small observational studies from the Netherlands, Spain and Canada also explored the effectiveness of using POCT in pharmacies for early detection of CKD and identification of nephrotoxic medication use,26–28 while an Australian study evaluated the feasibility of a pharmacist-led CKD screening 29…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation